(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
Starting with Virginia Wolf’s question which gives name to her essay How should one read a book? and her vivid interest in the figure of the common reader, this article aims to displace her analytical approach from the literary field to the theatrical field, so as to problematize the spectator figure. Intending to investigate the singularities and potentialities which are invested in the eyes of common spectators (deliberately focused as a spectator of whatever-singularity here), the article mobilizes two characters: a critic who is described as an ideal spectator in Diderot’s Discourse on Dramatic Poetry; and a prostitute who is passionate about Greek tragedies, played by the actress Melina Mercouri on Jules Dassin’s movie Never on Sunday. Seeking to distinguish the eye of the common spectator from the eye of that who is supposed to be his opposite - the specialist -, this article indicates two distinctive procedures both present in the relationship between regard and work of art: the hermeneutic gesture that articulates knowledge from a transcendental field and the whatever-singularity gesture that refuses exteriorities and establishes a sphere of immanence.